Storing Plantain Using A Traditional Cold Jar - Kouadio Kouakou K.A; Kone M. B; Soro L. C; Ocho -Anin Atchibri L (International Journal of Science and Environment (IJSE), 2022)
Optimizing the use of plantains depends not only on increasing its production but also on improving post-harvest operations before it reaches the final consumer. Proper management during the post-harvest period is better than using advanced technology. Themain objective of this study is to preserve plantains in a traditional cold pot in the locality of Man. To carry out this experiment, we used a device consisting of a large pot containing a small pot and clay filling the space between the pot and the large pot. This device, commonly known as the “desert fridge”, has enabled us to obtain green lifespans for the Corne 1 and Agnrin cultivars of between 15 and 22 days. During our conservation, the physical and biochemical characteristics of plantains were determined. The analyzes revealed a slight lower mass loss: Horn 1 (6.85 ±0.2%) and Agnrin (7.4 ±0.5%), loss of firmness and dry matter, reduction in starches and dietary fiber. But on the other hand, an increase in the content of reducing sugars, the transfer of the color of the skin from green to yellow of the stored plantains.